Molecular and functional changes in neutrophilic granulocytes induced by nicotine: a systematic review and critical evaluation - Brembach, Theresa-Charlotte; Sabat, Robert; Witte, Katrin; Schwerdtle, Tanja; Wolk, Kerstin (Frontiers in Immunology, 2023)
Background Over 1.1 billion people smoke worldwide. The alkaloid nicotine is a prominent and addictive component of tobacco. In addition to tumors and cardiovascular disorders, tobacco consumption is associated with a variety of chronic-inflammatory diseases. Although neutrophilic granulocytes (neutrophils) play a role in the pathogenesis of many of these diseases, the impact of nicotine on neutrophils has not been systematically reviewed so far. Objectives The aim of this systematic review was to evaluate the direct influence of nicotine on human neutrophil functions, specifically on cell death/damage, apoptosis, chemotaxis, general motility, adhesion molecule expression, eicosanoid synthesis, cytokine/chemokine expression, formation of neutrophil extracellular traps (NETs), phagocytosis, generation of reactive oxygen species (ROS), net antimicrobial activity, and enzyme release. Material and methods This review was conducted according to the PRISMA guidelines. A literature search was performed in the databases NCBI Pubmed® and Web of Science™ in February 2023. Inclusion criteria comprised English written research articles, showing in vitro studies on the direct impact of nicotine on specified human neutrophil functions. Results Of the 532 originally identified articles, data from 34 articles were finally compiled after several evaluation steps. The considered studies highly varied in methodological aspects. While at high concentrations (>3 mmol/l) nicotine started to be cytotoxic to neutrophils, concentrations typically achieved in blood of smokers (in the nmol/l range) applied for long exposure times (24-72h) supported the survival of neutrophils. Smoking-relevant nicotine concentrations also increased the chemotaxis of neutrophils towards several chemoattractants, elevated their production of elastase, lipocalin-2, CXCL8, leukotriene B4 and prostaglandin E2, and reduced their integrin expression. Moreover, while nicotine impaired the neutrophil phagocytotic and anti-microbial activity, a range of studies demonstrated increased NET formation. However, conflicting effects were found on ROS generation, selectin expression and release of β-glucuronidase and myeloperoxidase. Conclusion Nicotine seems to support the presence in the tissue and the inflammatory and selected tissue-damaging activity of neutrophils and reduces their antimicrobial functions, suggesting a direct contribution of nicotine to the pathogenesis of chronic-inflammatory diseases via influencing the neutrophil biology.